The Role and Influence of the Principal's Work Ethics in Improving the Quality of Islamic Education - Nurhaelah Nurhaelah; Astuti Darmiyanti; Saprialman Saprialman (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2023)
The principal's work ethic is a work norm or standard that must be met and implemented by the principal in order to create a quality and quality school. The principal plays a role in all aspects of the school, including in school development and related to improving the quality of education. The quality of education is a school's ability in overall management of everything related to the school which will then produce quality output. The quality of Islamic education is very important in an Islamic educational institution, as is the case with education in general, where the quality must have high quality or experience quality improvement for the advancement of Islamic education. Islamic education will produce a nation's next generation who can compete well in the era of globalization, namely by being equipped with an understanding of religious knowledge and general knowledge, so that their knowledge balances between world knowledge and knowledge of the hereafter. The role of the school principal is very influential in improving the quality of Islamic education, where the principal must have the ability to manage his performance properly, besides that the principal is also required to always find innovation so that the quality of Islamic education can be further improved, but it must be based on Islamic laws.